The Problem of Expression of Speculative Concreteness in the “Phenomenology of Spirit” and Hegel’s Understanding of the Nature and Limits of Philosophical Knowledge - Vyacheslav I. Korotkikh (RUDN Journal of Philosophy)
The research analyzes such an aspect of the «Phenomenology of Spirit» as the influence of the search for a form of expression of the «experience of consciousness» on the formation of the notion of philosophy. The basis of Hegel’s search is the idea of the identity of thought and language, which is reflected in the «inner speech». Testing the content of «experience» by speech removes from philosophy everything that goes beyond the limits of thought. However, in each of the three «circles» of «Phenomenology», «inner speech» is insufficient to express speculative concreteness. In these fragments, the form of the description approaches the model of philosophy, which was associated in the culture of the Hegelian era with intellectual intuition. The rejection of intuition and the describing of the content of self-consciousness in the process of its social activity create the danger of losing the unity, which is an essential feature of philosophical knowledge. Hegel finds a solution to this problem in building a composition of the work that is based on the consistent distinction and interaction of the subjects of «experience», which play a different role in moving towards the common purpose. As a result, the various socio-cultural content of «experience» in «recollection-inwardizing» takes the form of a «concept», that is accepted by Hegel as adequate to the nature of philosophical knowledge.